Representation of Conventional Gender Roles in Prasad - Bista, Asmita (Dristikon: A Multidisciplinary Journal, 2021)
The film Prasad reveals the prevailed gender practices in Nepali society that instigate to perform the stereotyped gender roles to the characters. So, the study aims to investigate how do characters construct the conventional gender identities. Likewise, this article intends to assess the reasons that force the characters to firmly stick to the prescribed gender roles. Similarly, to examine the consequences the characters go through while performing the traditional gender roles, is another objective of this article. To meet these objectives, Gender studies has been used as theoretical tools. Particularly, Judith Butler’s, and R.W. Connell’s idea of gender theory has been used. These theorists propose theory of gender as constructed phenomenon that is achieved through the constant performance. This article contributes to understanding the harmful consequences caused by conventional gender roles to the people. The study concludes that assigning the stereotyped gender roles to the characters, the film Prasad indorses the existing gender stereotype.